2015
DOI: 10.1128/jcm.01853-14
|View full text |Cite
|
Sign up to set email alerts
|

A Valuable Antigen Detection Method for Diagnosis of Acute Hepatitis E

Abstract: Hepatitis E virus (HEV) is a serious public health problem. The commonly used tests that are specific for current HEV infection diagnosis include the detection of anti-HEV IgM and HEV RNA. Here, we report an improved enzyme-linked immunosorbent assay (ELISA) method for HEV antigen detection with a linear range equivalent to 6.3 ؋ 10 3 to 9.2 ؋ 10 5 RNA copies per ml. The monoclonal antibody (MAb) 12F12, a high-ability MAb that binds HEV virus, was selected as the capture antibody from a panel of 95 MAbs. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 20 publications
4
47
0
Order By: Relevance
“…This indicates HEV antigen is likely to persist for a short period, and is undetectable by the time of appearance of HEV IgM. A study has shown that 19% (3/16) of HEV antigen positive samples were HEV IgM negative [27]. Concurrent detection of HEV antigen and IgG in both our donors could indicate re-infection, however, non-specificity of the antigen assay cannot be ruled out.…”
Section: Discussionmentioning
confidence: 91%
“…This indicates HEV antigen is likely to persist for a short period, and is undetectable by the time of appearance of HEV IgM. A study has shown that 19% (3/16) of HEV antigen positive samples were HEV IgM negative [27]. Concurrent detection of HEV antigen and IgG in both our donors could indicate re-infection, however, non-specificity of the antigen assay cannot be ruled out.…”
Section: Discussionmentioning
confidence: 91%
“…A recombinant ORF2 dimer (rDimer) comprising amino acids 394-606 was also included (21). mAbs 12F12 and #4, which are used in the commercial HEV antigen ELISA (25), recognized all four forms of ORF2 (rVLP, rDimer, ORF2 S , and virions) of all genotypes tested (g1, g3, and g4), therefore were used to adjust the input amounts of different ORF2 forms.…”
Section: Significancementioning
confidence: 99%
“…Recently, a test to detect HEV antigen (HEV‐Ag) has been developed and assessed for HEV diagnosis . A potential advantage of HEV‐Ag is that it is detectable prior to ALT elevation and development of anti‐HEV antibodies, although this finding is supported by only a few studies . The aims of our study were (a) to analyse the duration of two different anti‐HEV IgM assays (Mikrogen and Wantai) in patients with self‐limited acute hepatitis E and (b) to assess the performance of anti‐HEV IgM and HEV‐Ag in this cohort in comparison with a group of subjects with transient HEV infection, defined by HEV RNA positive.…”
Section: Introductionmentioning
confidence: 99%